Deploying SharePoint 2016 Best Practices for Installing, Configuring, and Maintaining SharePoint Server 2016 - Catrinescu, Vlad; Seward, Trevor (Apress : Imprint: Apress, 2016)
Learn how to install, configure, and maintain the latest release of Microsoft's popular SharePoint Server, SharePoint 2016. This latest version brings with it many changes for IT professionals. With this book you will learn how to create an efficient and stable SharePoint environment for your organization. Deploying SharePoint 2016 will help you: Learn the steps to install SharePoint Server 2016, using both the user interface provided by Microsoft, and PowerShell Understand your authentication options and associated security considerations Deploy add-ins, either from the store, or from your own custom app catalog Configure Search Service Application using either the provided user interface (UI) or PowerShell Configure business intelligence service applications such as SSRS, PowerPivot, and Performance Point Learn the steps to migrate to SharePoint Server 2016 from either SharePoint Server 2010 or 2013 Understand the approaches to high availability, disaster recovery, patching, and ways to monitor and maintain your SharePoint 2016 deployment once it's up and running Who This Book Is For: Anyone tasked with installing, configuring, and maintaining SharePoint Server 2016 in their organization. This book assumes some working knowledge of previous release of SharePoint Server, such as SharePoint 2010 or SharePoint 2013.